Prophecy and progress : - Kumar, Krishan (Penguin Books, 1978)
Takes a look at industrial society, past and present, in order to evaluate the claims about its possible future. The author begins with the industrial revolution itself, examining the ideas it inspired, and then moves on to post-industrial ideas.